Severe gangrene by cold agglutinemia - Vicari,Perla (2004)
The cold agglutinin syndrome is a haemolytic disorder usually manifested by acrocyanosis and Raynaud's phenomenon. Gangrene is an uncommon complication, usually associated with infections or B-cell lymphoproliferative diseases. We present a case of fulminant gangrene of fingers, toes, and nose in a 77-year-old woman with atypical pneumonia and acute renal failure. The diagnosis of haemolytic anaemia with cold agglutinin syndrome was done and the treatment with antibiotics and corticosteroids was effective. However, amputation of all the toes on both feet could not be avoided. Clinical aspects of cold agglutinemia, transient or chronic, are briefly discussed. We conclude that, in the presence of cold agglutinin syndrome, the treatment should be promptly initiated in order to avoid complications such as extensive gangrene.